Site-specific phosphorylation regulates the structure and function of an intrinsically disordered domain of the glucocorticoid receptor. Issue 1 (December 2017) - Khan, Shagufta; McLaughlin, William; Kumar, Raj
Abstract Intrinsically disordered (ID) regions of the transcription factor proteins have much larger frequency of phosphorylation sites than ordered regions, suggesting an important role in their regulatory capacity. Consistent with this phenomenon, most of the functionally known phosphorylation sites in the steroid receptor family of transcription factors are located in the ID N-terminal domain that contains a powerful activation function (AF1) region. In this study, we determined the structural and functional consequences of functionally known phosphorylation residues (Ser203, 211, and 226) located in the human glucocorticoid receptor's (GR's) ID AF1 domain. We report the relative importance of each phosphorylation site in inducing a functionally active ordered conformation in GR's ID AF1 domain. Our data demonstrate a mechanism through which ID domain of the steroid receptors and other similar transcription factors may adopt a functionally active conformation under physiological conditions.